(untitled) (Costos y Gestión, 2019)
Corporate Social Responsibility (CSR) is a management approach or philosophy that in recent decades has experienced a remarkable development. In general, it refers to the policies and actions that companies must develop to achieve economic, social and environmental improvements in order to expand their competitive situation, their added value and consequently their sustainability. The objective of this paper is to reflect on the recognition of Social and Environmental Accounting as a segment of Accounting, about its content and link with stakeholder theory, its usefulness in social and environmental organizational decision making process, as well as the role played in recent years by regulatory entities in relation to the reference issue. The authors conclude that it is a discipline approach that shares content with the Financial Accounting and Management segments, reflecting on certain “limitations in scope” when it comes to managing and managing a topic so sensitive to the global community.